AN ENHANCED CLASSIFICATION AND REGRESSION TREE ALGORITHM USING GINI EXPONENTIAL - Bello, Safinatu; Aliyu, Ahmad Abubakar; Ahmad, Muhammad Aminu; Abdullahi, Adamu; Abdulkadir, Sa’adatu; Ahmed, Abubakar Muazu; Dauda, Suleiman (FUDMA JOURNAL OF SCIENCES, 2025)
Decision tree algorithms, particularly Classification and Regression Trees (CART), are widely used in machine learning for their simplicity, interpretability, and ability to handle both categorical and numerical data. However, traditional decision trees often encounter limitations when dealing with complex, high-dimensional, or imbalanced datasets, as conventional impurity measures such as the Gini Index and Information Gain may fail to capture subtle variations in the data effectively. This study enhances the traditional Classification and Regression Trees (CART) model by introducing the Gini Exponential Criterion, which incorporates an exponential weighting factor into the split point calculation process. This novel approach amplifies the influence of highly discriminative features, resulting in more refined splits and improved decision boundaries. The enhanced CART model was evaluated on two benchmark datasets: the wine quality dataset and the hypothyroid dataset, with preprocessing steps like feature scaling and SMOTE for class imbalance, and hyperparameter tuning via Bayesian Optimization. On the wine quality dataset, the enhanced model improved accuracy from 57% (traditional CART) to 86%, while on the hypothyroid dataset, it achieved an impressive accuracy of 98%. These results highlight the model’s ability to handle complex and imbalanced data effectively. Feature importance analysis and decision tree visualization further demonstrated the model’s interpretability. The study concludes that the Gini Exponential Criterion significantly improves CART’s performance, offering better generalization and clearer decision boundaries. This advancement is particularly valuable for applications requiring precise and interpretable predictions, such as healthcare diagnostics and quality assessment. Future work could explore integrating this criterion into ensemble methods and...